2012
DOI: 10.1029/2012gl051480
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pore‐pressure on the event‐size distribution of induced earthquakes

Abstract: [1] During an Enhanced Geothermal System (EGS) experiment, fluid is injected at high pressure into crystalline rock, to enhance its permeability and thus create a reservoir from which geothermal heat can be extracted. The fracturing of the basement caused by these high pore-pressures is associated with microseismicity. However, the relationship between the magnitudes of these induced seismic events and the applied fluid injection rates, and thus pore-pressure, is unknown. Here we show how pore-pressure can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
187
5

Year Published

2013
2013
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 222 publications
(232 citation statements)
references
References 31 publications
26
187
5
Order By: Relevance
“…Isotropic moment tensor components may relate to the occurrence of long-period events (Bame and Fehler, 1986;Ferrazzini et al, 1990;Jousset et al, 2010). The locations of the events with high isotropic components also coincide with previously found regions of high -values (Bachmann et al, 2012) and low stress drops (Goertz-Allmann et al, 2011).…”
Section: Basel Switzerlandsupporting
confidence: 64%
See 1 more Smart Citation
“…Isotropic moment tensor components may relate to the occurrence of long-period events (Bame and Fehler, 1986;Ferrazzini et al, 1990;Jousset et al, 2010). The locations of the events with high isotropic components also coincide with previously found regions of high -values (Bachmann et al, 2012) and low stress drops (Goertz-Allmann et al, 2011).…”
Section: Basel Switzerlandsupporting
confidence: 64%
“…The results of a high-resolution -value mapping by Bachmann et al (2012) are summarized in Fig. 6, which shows the highly-systematic spatial heterogeneity of the -values associated with the seismicity induced by the Basel EGS.…”
Section: Basel Switzerlandmentioning
confidence: 99%
“…Goertz-Allmann and Wiemer (2012) found a substantial increase of the mean probability for the time period after shut-in and also at further distances from the injection point, compared to a constant b-value model. Their results not only explained the observations at Basel (GoertzAllmann et al 2011, Bachmann et al 2012), but were also consistent with observations at other geothermal projects (Kwiatek et al 2013, Charlety et al 2007, Evans et al 2012). The presented modeling and magnitude probability estimation technique could be used in a refined traffic light system, where the future induced seismicity magnitude probability is estimated based on the previously recorded seismicity of an ongoing operation.…”
Section: Characterization Of Large Magnitude Events (Lme)supporting
confidence: 80%
“…Spatial variations of source parameters such as stress drop and b-value of the Basel induced seismicity have been estimated by Goertz-Allmann et al (2011) and Bachmann et al (2012), respectively. It has been observed that stress drops are greatly reduced and b-values increases in the vicinity of the injection point where pore pressures are highest.…”
Section: Characterization Of Large Magnitude Events (Lme)mentioning
confidence: 99%
“…to or larger than those for tectonic earthquakes [Shapiro et al, 2011;Bachmann et al, 2012]; however, studies on induced earthquakes in hydrocarbon reservoirs have found lower values [Friberg et al, 2014;Skoumal et al, 2014Skoumal et al, , 2015. Rabak et al [2010] observe a b value of 0.9 for the 2011 Enola swarm (~20 km southeast of the Guy-Greenbrier region) and speculate that natural fluid migration may trigger the swarm.…”
Section: 1002/2015gl065170mentioning
confidence: 99%